A two-step gas/liquid strategy for the production of N-doped defect-rich transition metal dichalcogenide nanosheets and their antibacterial applications. Issue 15 (2nd April 2020) - Wang, Tao; Zhang, Xiao; Mei, Linqiang; Ma, Dongqing; Liao, You; Zu, Yan; Xu, Peng; Yin, Wenyan; Gu, Zhanjun
Abstract : A simple two-step strategy based on gas expansion combined liquid exfoliation to synthesize defect-rich N-doped MoS2 and N-doped WS2 nanosheets (NSs) was proposed. The NSs with improved peroxidase-like catalytic activity can be applied as effective nanoantimicrobials. Abstract : Herein, we developed a general two-step gas expansion and exfoliation strategy based on a urea-assisted hydrothermal process combined with sonication exfoliation for the production of nitrogen (N)-doped plus defect-rich transition metal dichalcogenide (TMD) nanosheets (NSs) such as N–MoS2 and N–WS2 NSs. The interlayers of bulk MoS2 (or WS2 ) were expanded with urea molecules dissolved in distilled water, which were decomposed to NH3 during the hydrothermal process. Simultaneously, sulfur atoms were partly replaced by N atoms to achieve N doping. Subsequently, sonication exfoliation of the urea-treated bulk MoS2 (or WS2 ) promoted the production of defect-rich NSs. Importantly, the defect-rich N–MoS2 and N–WS2 NSs exhibit enhanced peroxidase-like catalytic activity after being captured by bacteria, and can catalyze hydrogen peroxide (H2 O2 ) to produce more toxic hydroxyl radicals (˙OH) than non-N-doped MoS2 or WS2 NSs. As a result, the N–MoS2 or N–WS2 NSs were capable of effectively killing Gram-negative ampicillin resistant Escherichia coli (Amp r E. coli ) and Gram-positive endospore-forming Bacillus subtilis ( B. subtilis ) and promoting bacteria-infected wound healing. This work not only provides a simple, universal exfoliation strategy for producing defect-rich N-doped TMD NSs but also provides a promising catalytic antibacterial option and has potential for many other catalytic applications.